RESIDENTIAL REAL ESTATE MARKET IN THE LARGEST CITIES OF RUSSIA: EVALUATION AND POSSIBILITIES OF ITS REGULATION - Glebova; Berman; Abdulganiev; Khafizova (Revista Inclusiones, 2019)
Improving the affordability of housing for various population categories is a main task of modern housing policy in Russia. The concept of housing affordability is considered in the broadest socioeconomic context, including not only the affordability of buying housing on the market, but also the possibility of obtaining free social housing for welfare beneficiaries, providing housing for service members, as well as rehousing citizens and etc. With the development of the housing market, the affordability degree for the population to buy housing to own is becoming increasingly important, especially since the share of private housing in the entire housing stock of Russia is very large - 86.3%, including 82.9% by right of ownership.